Remarkable Cd-free Sb2Se3 solar cell yield achieved by interface band-alignment and growth orientation screening. Issue 47 (25th November 2021) - Wang, Weihuang; Cao, Zixiu; Wang, Huanhuan; Luo, Jingshan; Zhang, Yi
Abstract : TiCl4 post-treatment on TiO2 ETL can significantly improve the conduction band alignment of TiO2 /Sb2 Se3 interface and tailor the growth orientation of Sb2 Se3 thin film by incorporating of Cl element at TiO2 /Sb2 Se3 interface and enhancing the (101) orientation of TiO2 . Abstract : Sb2 Se3 has attracted a lot of attention in recent years owing to its excellent photoelectrical properties. Eco-friendly TiO2, with its wide band gap, is a promising candidate for the electron transporting layer (ETL) of Cd-free Sb2 Se3 solar cells. However, the undesirable band alignment of the TiO2 /Sb2 Se3 interface hinders its wide application. Herein, a TiCl4 -passivated TiO2 ETL was introduced to solve this problem. The incorporation of Cl atoms leads to the enhanced (101) orientation of anatase TiO2, by which the growth orientation of the Sb2 Se3 film could be effectively tailored. The performance of the Sb2 Se3 device with TiCl4 treatment was dramatically enhanced by the improved band alignment at the TiO2 /Sb2 Se3 interface, decreased interface defects, a pinhole-free ETL and enhanced crystal orientation. Finally, the synergetic improvement of the device parameters yielded a best device efficiency of 5.33% for a configuration of ITO/TiO2 /Sb2 Se3 /Au. In this configuration, the preferred band offset renders the highest open circuit voltage ( V oc ) value (394 mV) in a Cd-free Sb2 Se3 solar cell processed using vapor transport deposition (VTD). This work is expected to provide helpful guidance for future experimental efforts to improve Cd-free device performance and interface quality.